1995
DOI: 10.1007/bf00029990
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of micropropagated buds of six woody species

Abstract: Regrowth after encapsulation in a sodium alginate matrix of micropropagated buds from six different in vitro proliferated woody species was evaluated. Actinidia deliciosa Liang & Ferguson (kiwifruit), Betula pendula Roth (birch), Crataegus oxyacantha L. (hawthorn), Malus spp. (apple), Rubus spp. (blackberry) and Rubus idaeus L. (raspberry) propagated in vitro were used as bud sources. Encapsulation with sodium alginate and subsequent regrowth on nutrient rich medium was compared to encapsulation with nutrient-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 6 publications
2
39
1
Order By: Relevance
“…The use of ABA as a growth retardant might contribute to a new understanding of the optimization of storage conditions in certain plant species, having highly active meristematic tissues for germination within hollow gel beads soon after encapsulation. There are several reports on synthetic seed production of fruit plants based on in vitro conservation and storage at 4 °C, including pomegranate (Naik and Chand, 2006), mulberry (Kavyashree et al, 2006), raspberry (Piccioni and Standardi, 1995), and black nightshade (Verma et al, 2010). Plant genotype, explant type, concentration of mineral contents, and/or sucrose in medium storage conditions and growth regulators are crucial for testing the viability and conservation of synthetic seeds (Benelli et al, 2013;Sharma et al, 2013;Berjak et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The use of ABA as a growth retardant might contribute to a new understanding of the optimization of storage conditions in certain plant species, having highly active meristematic tissues for germination within hollow gel beads soon after encapsulation. There are several reports on synthetic seed production of fruit plants based on in vitro conservation and storage at 4 °C, including pomegranate (Naik and Chand, 2006), mulberry (Kavyashree et al, 2006), raspberry (Piccioni and Standardi, 1995), and black nightshade (Verma et al, 2010). Plant genotype, explant type, concentration of mineral contents, and/or sucrose in medium storage conditions and growth regulators are crucial for testing the viability and conservation of synthetic seeds (Benelli et al, 2013;Sharma et al, 2013;Berjak et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In some species, such as banana, cardamom, mulberry and raspberry, encapsulated microcuttings demonstrated high adventitious rooting capacity after sowing [14,24,25], while other species did not respond [23,26]. There are many factors affect the conversion of synseeds after cold storage period.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Mathur et al (1989) reported that the use of this technology economized upon the medium, space and time requirements. Successful cases of synthetic seeds production and plantlet regeneration have been reported for cereals, vegetables, fruits, ornamentals, aromatic grass and conifers (Fowke et al, 1994;Piccioni and Standardi, 1995;Castillo et al, 1998;Ganapathi et al, 2001;Brischia et al, 2002;Hao and Deng, 2003). However, in most cases somatic embryos were used in the encapsulation process.…”
Section: Introductionmentioning
confidence: 99%
“…However, in most cases somatic embryos were used in the encapsulation process. Some authors (Mathur et al, 1989;Ganapathi et al, 1992;Sharma et al, 1994;Piccioni and Standardi, 1995;Pattnaik and Chand, 2000) described the encapsulation of vegetative propagules such as axillary buds or shoot tips, which could be used for mass clonal propagation as well as in longterm conservation of germplasm.…”
Section: Introductionmentioning
confidence: 99%